Determination of the optical constants of Co(II) complex of Schiff base obtained from 1,8-diaminonaphthalene thin film by infrared spectra - Yakuphanoğlu, Fahrettin; Sekerci, M (Elsevier, 2005)
Determination of optical constants of metal complex thin film has been investigated by reflectance and transmittance spectra. The optical constants (refractive index n, extinction coefficient k, and dielectric constant epsilon) of the thin film were determined. The real part and imaginary parts of the complex dielectric constant were calculated. The refractive index dispersion obeyed the Cauchy model and Cauchy parameters were determined as A = 13.17, B = 9.37 X 10(-6) cm(2) and C = 1.58 X 10(-13) cm(4) at the range of 1700-4000 cm(-1). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: thin film; refractive index dispersion; complex dielectric constant